Perencanaan Peningkatan Kualitas dengan Menggunakan Integrasi Metode Six Sigma dan ISO 9001:2000 - Imron Kuswandi (Jurnal Teknik Industri, 2009)
Companies who produce several of cigarettes, one of the kinds is BM Universal 12. To produce product with best quality and due to give satisfaction toward its consumer, there are several problem faced by the cigarette production process which is there are still defect product in its production process. From this condition, they need one method to deal with the matter. Using six sigma methods, they can identify defect product and by doing that they could improve the quality of the product. In this experiment it's using integration method by combining six sigma method and ISO 9001:2000. Six sigma methods is expected to be able minimizing the defect in PT "X" by creating production process more effectively, better performance of the company and still fulfilling the need and the satisfaction of the consumer while also making efforts to improve and inclined its quality. Meanwhile ISO 9001:2000, is an international standard that has orientation toward the qualifying products. Based on its internal data and observation commence inside the company, there would be only three main clauses from ISO 9001:2000 requirements that is going to be made as measuring points of product quality improvement, which is clause 5 (management responsibilities), 7 (product realization) and 8 (measurement, analysis and improvement). While Six Sigma phase comprises of Define, Measure, Analyze and Improve. In Define phase there would be defining the product, the making of Six Sigma team and the making of production flow process. Measure has 3 kind defects that usually have bigger percentage than other defects which is unbalance weight defect (including empty shell) and korep defect. The percentage that goes with unbalance weight defect (including empty shell) is 41.9% and korep defect with 21.03% from all three defect we gained DPMO value reaching 7776 and sigma level reaching 3,9. By viewing the FMEA and RPN, the improvement alternatives that suppose to be done by the company is creating job instruction, implementing job instruction in rolling process then the company should be able to save Rp3,942,975.00 for one month.